The Paranormal in Shakespeare’s Plays - Saud, Raj Kumar (KVM Research Journal, 2025)
This essay examines Shakespeare’s plays’ supernatural themes from a number of angles. Shakespeare’s literary career’s historical context is first introduced. Next, it examines the supernatural themes found in three of his best plays and presents the ways in which the supernatural is portrayed on stage in both the Elizabethan era and the present. Finally, it offers spectators of Shakespeare’s plays in the twentyfirst century the contemporary ramifications.